Particulate Th-234, organic carbon, organic nitrogen and biogenic silica concentrations in size-fractionated particles in the Labrador Sea in spring 2022 - Montserrat Roca-Martí; Madeline Healey; Stephanie S Kienast (PANGAEA, 2025)
Particulate Th-234, organic carbon (POC), organic nitrogen (PON) and biogenic silica (bSi) concentrations in size-fractionated particles in the Labrador Sea from 19 May to 2 June 2022 during the BELAS-1 expedition (CE22009, RV Celtic Explorer). Size-fractionated particles were collected using battery-powered in-situ large volume pumps (McLane Research Laboratories, Inc.) equipped with a three-tier 142-mm diameter filter holder (MULVFS style; Bishop et al., 2012; Lam et al., 2015). Pumps were deployed at depths between 50 and 500 m. The filter holders contained three filters: two Nitex screens (335 and 51 μm nominal pore size, acid-leached prior to the cruise) above a pre-combusted QMA filter (~1 μm nominal pore size, Graff et al., 2023) for size fractionation (1–51, 51–335 and >335 μm). Th-234 was measured using low-level Risø beta multicounters. POC and PON were analyzed using high-temperature combustion (Costech Instruments Elemental Combustion System 4010) after acid fumigation. bSi was analyzed following the NaOH digestion method (40 min at 95C) using a UV-Visible Spectrophotometer (Genesys 10S, Thermo Scientific).